The genera Egmundella Stechow, 1921 and Cyclocanna Bigelow, 1918 (Cnidaria, Hydrozoa) in waters of Northwest Africa - Gil, Marta; Ramil, Fran (Zootaxa, 2023)
In this paper, we study material belonging to the hydroid genera Egmundella Stechow, 1921 and Cyclocanna Bigelow, 1918 collected off the coast of Northwest Africa, from Morocco to Guinea Bissau, between 2004 and 2012, during several international surveys. Currently, the genus Egmundella is included in the family Campanulinidae Hincks, 1869, but its taxonomic status is doubtful, since most of the life cycles of its species are unknown. A total of four species have been identified: E. grimaldii Leloup, 1940, E. modesta Millard & Bouillon, 1975, E. superba Stechow, 1921 and E. ansini n. sp. Egmundella grimaldii is found for the first time since its original description, and fertile material is described herein. Its gonotheca is morphologically similar to that of C. producta (G.O. Sars, 1874), suggesting that both species could be congeneric. A description of specimens of C. producta collected along the NW African coast is also provided.